Long-term efficacy of spasticity-corrective surgery and botulinum toxin injections for upper limb spasticity treatment - Therese Ramström; Johanna Wangdell; Carina Reinholdt; Trandur Ulfarsson; Lina Bunketorp Käll (Journal of Rehabilitation Medicine - Clinical Communications)
Objective: To evaluate the long-term efficacy of spasticity-corrective surgery and botulinum toxin treatment in patients with upper limb spasticity.